Quale tutela delle libertà fondamentali per i simboli religiosi? Considerazioni sulla decisione del Consiglio di Stato francese sul caso burkini (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Premessa - 2. Luoghi pubblici e simboli religiosi - 3. Rispetto del dialogo e delle diversità interculturali - 4. L’evoluzione della laicità in Europa - 5. Osservazioni conclusive.Which protection for the fundamental freedom of religious symbols?Abstract: Starting from the analysis of the French Council of State’s decision on the case “burkini” (August 26th 2016), this paper examines the issues on the interaction between the acceptance of the religious minority’s symbols by the majority and the acceptance of the dialogue and cultural diversity. Taken into account is the process of secularism-neutrality of public space and the interference of the civil judiciary in the religious sphere declined in different models of secularism of the French, Italian and European jurisdictions.